Pengaruh Pembelajaran Berbentuk Simulasi Modellus Terhadap Peningkatan Pemahaman Konsep Gerak Parabola - Febriana, Nur (Jurnal Pendidikan Madrasah, 2023)
This study aims to explore the influence of learning using Modellus on the understanding of the concept of parabolic motion of students at SMA Negeri 1 Sanden compared to conventional learning, the influence of learning using Modellus on increasing interest in learning physics, and the angle of elevation on distance traveled using Modellus. Data collection was carried out by conducting pretest and post-test on the understanding of parabolic motion in both classes. Data analysis was performed using ANOVA analysis. The results showed that the use of learning models in the form of simulations to increase understanding of the concept of parabolic motion compared to conventional learning models.